Increased prevalence of late stage T cell activation antigen (VLA-1) in active juvenile chronic arthritis. Issue 11 (November 1987) - Odum, N; Morling, N; Platz, P; Hofmann, B; Ryder, L P; Heilmann, C; Pedersen, F K; Nielsen, L P; Friis, J; Svejgaard, A
Abstract : The presence of activated T cells as judged from the reaction with monoclonal antibodies (MoAb) against (a) a late stage T cell activation antigen (VLA-1), (b) the interleukin 2 (IL2) receptor (CD25), and (c) four different HLA class II molecules (HLA-DR, DRw52, DQ, and DP) was studied in 15 patients with active juvenile chronic arthritis (JCA), 10 patients with JCA in remission, and 11 age matched, healthy controls. In addition, the distribution of T 'helper/inducer' (CD4+), T 'suppressor/inducer' (CD4+, Leu8+), T 'suppressor/cytotoxic' (CD8+), and 'natural killer' (NK) cells (CD16+) was studied. Twenty patients and six controls were investigated for the capability to stimulate alloreactivated primed lymphocytes. The prevalence of VLA-1 positive, large cells was significantly increased to 5% (median value) in active JCA as compared with JCA in remission (2%, p less than 0.05) and controls (1%, p less than 0.05), whereas no significant difference between JCA in remission and controls was observed. Except for two patients with active JCA, less than 1% IL2 receptor bearing cells were found in patients with JCA and controls. No significant difference in the prevalence and expression of the various HLA class II antigens was observed between the groups. Similarly, no significant differences in stimulatory capability in secondary mixed lymphocyte culture (MLC) were seen. The distribution of T helper/inducer (CD4+), T suppressor/cytotoxic (CD8+), and NK cells was similar in active JCA, JCA in remission, and controls. The prevalence of T suppressor/inducer (CD4+, Leu8+) cells was higher in remission JCA (17%) than in active JCA (11%) and controls (10%). This increase, however, did not reach statistical significance. In conclusion, late stage but not early stage T cell activation antigens were increased in patients with active JCA as compared with patients with JCA in remission and control, whereas some patients in remission had an increased prevalence of T suppressor/inducer cells.